A ketamine package for use in emergency cesarean delivery when no anesthetist is available: An analysis of 401 consecutive operations. Issue 2 (28th October 2021) - Burke, Thomas F.; Mantena, Sreekar; Opondo, Kennedy; Orero, Solomon; Rogo, Khama
Abstract: Objective: To evaluate the safety and effectiveness of a ketamine‐based anesthesia package to support emergency cesarean section when no anesthetist is available. Methods: A prospective case‐series was conducted between December 11, 2013 and September 30, 2021 across nine sub‐county hospitals in Kenya. Non‐anesthetist healthcare providers undertook an evidence‐based five‐day training course. A structured instrument was used to collect preoperative, intraoperative, and postoperative data, and patients were contacted 6 months following the surgery to collect outcomes. The primary outcome measures were maternal and newborn survival and the ability of the ketamine package (ESM‐Ketamine) to safely support cesarean deliveries. Results: A total of 401 emergency cesarean sections were performed using ketamine, administered by 54 non‐anesthetist providers. All mothers survived to discharge. Brief oxygen desaturations were recorded among 33 (8.2%) mothers, and agitation and hallucinations occurred among 13 (3.2%). There were no maternal serious adverse events. At 6‐month follow‐up, 94.2% of mothers who could be reached reported no complaints. Additionally, 402 (92.4%) of the 435 operative births survived to discharge. Conclusion: The ESM‐Ketamine package can be used by trained non‐anesthetist providers to support emergency cesarean sections when no anesthetist is available. Ketamine has significant potential to increase access to emergency cesarean deliveries in resource‐limited settings. Abstract : A ketamine‐based anesthesia package was found to be safe and effective in support of 401 emergency cesarean sections when used by trained non‐anesthetist healthcare providers.